2004
DOI: 10.1103/physreve.70.066207
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation of underwater sand ripples with a skewed drive

Abstract: In this paper we present an experimental study of the dynamics of underwater sand ripples when a regular pattern of ripples is subjected to a skewed oscillatory flow, i.e., one not perpendicular to the direction of the ripple crests. Striking patterns with new, superposed ripples on top of the original ones occur very quickly with a characteristic angle, which is, in general, not perpendicular to the flow. A slower, more complex transition then follows, leading to the final state where the ripples are again pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Laboratory and theoretical studies of such types of ripples have shown that some 3D ripple types occur as stable bedforms under constant oscillatory-flow conditions (e.g. Bagnold, 1946;Silvester, 1972Silvester, , 1975Matsunaga and Honji, 1980;Vittori and Blondeaux, 1992;Jan and Lin, 1998;Roos and Blondeaux, 2001), but other types emerge as ephemeral features during the process of ripple deformation in response to a change in near-bottom flow conditions (Hansen et al, 2001a(Hansen et al, , 2001bBundgaard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory and theoretical studies of such types of ripples have shown that some 3D ripple types occur as stable bedforms under constant oscillatory-flow conditions (e.g. Bagnold, 1946;Silvester, 1972Silvester, , 1975Matsunaga and Honji, 1980;Vittori and Blondeaux, 1992;Jan and Lin, 1998;Roos and Blondeaux, 2001), but other types emerge as ephemeral features during the process of ripple deformation in response to a change in near-bottom flow conditions (Hansen et al, 2001a(Hansen et al, , 2001bBundgaard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It could be widely accepted that 3D-patterned transitional ripples appear after oscillatory flow changes from a direction that is perpendicular to the crest line of the pre-existing ripples to one that is oblique or parallel (Bundgaard et al, 2004). However, through their oscillatory-bed experiment, Hansen et al (2001aHansen et al ( , 2001b have shown that ephemeral 3D-patterned ripples emerge even when the oscillatory flow direction does not change.…”
Section: Introductionmentioning
confidence: 99%
“…, oscillatory-flow ripple , Nielsen, 1979Bagnold, 1946Traykovski et al, 1999Evans, 1943Shulyak, 1963Lofquist, 1978Traykovski et al 1999Hansen et al 2001a, b Bundgaard et al, 2004Davis et al, 2004;Sunamura, 2004, 2005;Sekiguchi, 2005Sekiguchi, , 2009Smith and Sleath, 2005;Testik et al, 2005;Doucette andO Donoghue, 2006 , Shulyak, 1963;Sekiguchi, 2005Sekiguchi, , 2009Davis et al, 2004;Sunamura, 2004, 2005;Testik et al, 2005Lofquist, 1978Doucette andO Donoghue, 2006 Hansen et al, 2001a, b;Bundgaard et al, 2004;Smith and Sleath, 2005 Hansen et al, 2001a, b;Bundgaard et al, 2004;Davis et al, 2004;Sekiguchi, 2005Sekiguchi, , 2009Sunamura, 2004, 2005;Smith and Sleath, 2005;Testik et al, 2005;Doucette and O Donoghue, 2006Bundgaard et al, 2004Hansen et al, 2001aSunamura, 2004, 2005 : λ e /λ i > λ e /λ i > 1 λ e Hansen et al, 2001a, b;Bundgaard et al, 2004;…”
mentioning
confidence: 99%